2021
DOI: 10.1002/bies.202100194
|View full text |Cite
|
Sign up to set email alerts
|

There is still no evidence of SARS‐CoV‐2 laboratory origin: Response to Segreto and Deigin (10.1002/bies.202100137)

Abstract: The causative agent of COVID-19 SARS-CoV-2 has led to over 4 million deaths worldwide. Understanding the origin of this coronavirus is important for the prevention of future outbreaks. The dominant point of view that the virus transferred to humans either directly from bats or through an intermediate mammalian host has been challenged by Segreto and Deigin, who claim that the genome of SARS-CoV-2 has certain features suggestive of its artificial creation. Following their response to our commentary, here we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The main point of criticism of our paper [1] expressed by Tyshkovskiy and Panchin in their commentary recently published by BioEssays [2] is based on a false premise: "the first major problem with Segreto's and Deigin's hypothesis is the significant divergence between the genome sequence of SARS-CoV-2 and its proposed ancestor RaTG13". The quoted statement is clearly false because we never claim that RaTG13 itself is a "proposed ancestor" or the backbone used for a possible construction of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The main point of criticism of our paper [1] expressed by Tyshkovskiy and Panchin in their commentary recently published by BioEssays [2] is based on a false premise: "the first major problem with Segreto's and Deigin's hypothesis is the significant divergence between the genome sequence of SARS-CoV-2 and its proposed ancestor RaTG13". The quoted statement is clearly false because we never claim that RaTG13 itself is a "proposed ancestor" or the backbone used for a possible construction of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 90%
“…In our paper "The genetic structure of SARS-CoV-2 does not rule out a genetic manipulation" [1] we describe several features of SARS-CoV-2 which could be consistent with a lab origin to demonstrate that the lab leak hypothesis cannot be dismissed as a conspiracy and should be investigated on par with a possible natural origin. Tyshkovskiy and Panchin have recently published a commentary in BioEssays [2] that attempts to criticize our paper and tries to dismiss the hypothesis that SARS-CoV-2 might have escaped from a laboratory. Herein we demonstrate that their commentary is built on the false premise that we have suggested RaTG13 to be a direct progenitor of SARS-CoV-2, and that other points of criticisms expressed by the authors are either irrelevant or not valid.…”
Section: Introductionmentioning
confidence: 99%
“…Further research indicated that a Horseshoe bat virus strain found in China's Yunnan Province has a genome similarity of 96.2% with SARS‐CoV‐2 (Zhou et al., 2020 ). Coincidentally, the later discovered that BANAL‐52 strain is 96.8% similar to SARS‐CoV‐2 (Tyshkovskiy & Panchin, 2021 ). These two strains are the most similar to SARS‐CoV‐2 reported to date, but the evidence to extrapolate from them is still very limited.…”
Section: Evidence From the Genome And Protein Structure Evolution Of ...mentioning
confidence: 99%
“…In addition, a furin site (TKRRSRR↓AI) was also detected in human intestinal coronaviruses (HECV‐4408, beta‐CoV) first in Germany in 1988 (Zhang, Herbst, Kousoulas, & Storz, 1994 ). Furthermore, other viruses, such as the H5 and H7 influenza viruses, have also been reported possessing a new multi‐base cleavage site that naturally arises by insertion (Decha et al., 2008 ; Garushyants, Rogozin, & Koonin, 2021 ; Taubenberger et al., 2005 ; Tyshkovskiy & Panchin, 2021 ).…”
Section: Evidence From the Genome And Protein Structure Evolution Of ...mentioning
confidence: 99%
See 1 more Smart Citation